Perceived Quality, Taste, And Price Perception Increase Repurchase Intention through customer Satisfaction - Indah Anjelia; Parlagutan Silitonga (Utan Kayu Publishing, 2025)
This study aims to identify the relationship between perceived quality, taste, and perceived price on customer satisfaction and repurchase intention at Soto Mie Bogor. The population in this study consisted of customers of Soto Mie Bogor. This study involved 246 respondents who were collected using questionnaire distribution with a purposive sampling technique. The purposive sampling requirement is that customers have visited Soto Mie Bogor, at least twice. Data analysis was carried out by Structural Equation Modeling (SEM) with the help of Smart-PLS software. The results showed that taste has a significant effect on customer satisfaction (t = 2.426, p = 0.016) and repurchase intention (t = 3.805, p = 0.000). Customer satisfaction also has a significant effect on repurchase intention (t = 4.382, p = 0.000). In addition, price perception has a positive and significant effect on customer satisfaction (t = 8.206, p = 0.000) and repurchase intention (t = 3.441, p = 0.001). In contrast, perceived quality has no significant effect on customer satisfaction (t = 1.689, p = 0.092) or repurchase intention (t = 0.757, p = 0.450). Analysis of indirect effects shows that taste affects repurchase intention through customer satisfaction has a significant effect (t = 2.298, p = 0.022), and perceived quality affects repurchase intention through customer satisfaction has no significant effect (t = 1.497, p = 0.135). Furthermore, price perception on repurchase intention through customer satisfaction has a significant effect (t = 3.788, p = 0.000).